Extent of Awareness of Distance Learners of Tamil Nadu Agricultural University - T R, Sridevi Krishnaveni; Balasubramaniam, P; Anusuya, A; Vasanthapriya, S (Journal of Extension Education, 2018)
The present research was framed to assess the awareness level of distance learners of Tamil Nadu Agricultural University. Three certificate courses were selected based on maximum number of enrollment, viz, Gardening & landscaping, Mushroom production & Solid waste management and vermicomposting. Ex-post facto research design was employed. A total of 150 respondents were selected from the three courses by equal allocation method proportionate random sampling. A well-structured questionnaire was prepared and the information was collected by sending questionnaires through post. The 108 individuals who responded were taken as the sample for the study. The results of the research pointed out that nearly three- fourths of the respondents possessed medium level of awareness on selected technologies.